2002
DOI: 10.1038/nn961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extensive temporal lobe damage or mild hypoxia on recollection and familiarity

Abstract: Memory for past events can be based on recollection or on assessments of familiarity. These two forms of human memory have been studied extensively by philosophers and psychologists, but their neuroanatomical substrates are largely unknown. Here we examined the brain regions that are involved in these two forms of memory by studying patients with damage to different temporal lobe regions. Our results come from (i) structural covariance modeling of recall and recognition, (ii) introspective reports during recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
495
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(541 citation statements)
references
References 40 publications
35
495
2
2
Order By: Relevance
“…Increased ER firing to repeats has been observed in monkeys when the repeated stimuli are also the behavioral targets (Suzuki et al, 1997). Some hemodynamic studies have found specific medial temporal activation during intentional recall and experiential recognition over implicit repetition, and lesion studies have found a specific deficit after medial temporal lesions in the same circumstances (Yonelinas et al, 2001;Yonelinas et al, 2002), but both findings are inconsistent (Squire et al, 2004). A variety of evidence in animals has led to the suggestion that familiarity/recognition depends on the repetition-induced decreases in cell firing in more lateral neocortical segments of the ventral temporal lobe, whereas conscious retrieval and recollection depends on medial structures, and especially the HC (Brown and Aggleton, 2001).…”
Section: Repetition and Retrieval Effectsmentioning
confidence: 99%
“…Increased ER firing to repeats has been observed in monkeys when the repeated stimuli are also the behavioral targets (Suzuki et al, 1997). Some hemodynamic studies have found specific medial temporal activation during intentional recall and experiential recognition over implicit repetition, and lesion studies have found a specific deficit after medial temporal lesions in the same circumstances (Yonelinas et al, 2001;Yonelinas et al, 2002), but both findings are inconsistent (Squire et al, 2004). A variety of evidence in animals has led to the suggestion that familiarity/recognition depends on the repetition-induced decreases in cell firing in more lateral neocortical segments of the ventral temporal lobe, whereas conscious retrieval and recollection depends on medial structures, and especially the HC (Brown and Aggleton, 2001).…”
Section: Repetition and Retrieval Effectsmentioning
confidence: 99%
“…Whereas, some studies have found clear visual item recognition deficits after relatively selective hippocampal damage (e.g., Cipolotti et al, 2001;Manns & Squire, 1999;Manns, Hopkins, Reed, Kitchener, & Squire, 2003;Reed & Squire, 1997), others have found little or no impairment in item recognition memory (Mayes, Holdstock, Isaac, Hunkin, & Roberts, 2002;Vargha-Khadem et al, 1997;Yonelinas et al, 2002). The explanation of these conflicting results is unknown, but most probably involves either differing extents and locations of hippocampal damage, differing extents of damage or dysfunction in extra-hippocampal sites critical for visual item recognition, or both (for example, see Baxter & Murray, 2001a and b;Zola & Squire, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence about whether hippocampal damage leaves familiarity memory intact is conflicting. Whereas, Yonelinas et al (2002) found, using several methods of assessment, that familiarity was preserved in patients who probably suffered hippocampal damage caused by hypoxia following a cardiac arrest, Manns et al (2003) found that familiarity was as impaired as recollection in a group of patients who had suffered hippocampal damage. Provided, as many researchers assume, that relatively normal item recognition memory can be supported by familiarity alone, the Aggleton and Brown hypothesis is consistent with hippocampal lesions causing only a mild item recognition deficit that might not be detectable in single patients.…”
Section: Introductionmentioning
confidence: 99%
“…Amnesia consequent to transient hypoxia associated with hippocampal damage results in a decrease in the asymmetry of the ROC function, reflecting a deficit in recollection, but the curvilinear shape is relatively spared, indicating that there is no effect on familiarity, whereas damage that reaches into the parahippocampal region results in deficits in both recollection and familiarity 4 , 5 . Our own ROC analyses, using an animal model where we definitively limited the damage to the hippocampus, resulted in a selective deficit in the same index of recollection (loss of asymmetry) and no impairment in familiarity (retained curvilinearity) 6 .…”
mentioning
confidence: 99%